Estudio de pre factibilidad para la implementación de una empresa productora de bocadillos a base de (panela, maní y maracuyá) en el cantón Paltas y su comercialización en la ciudad de Loja - Campoverde Cedeño, Jeniffer Mishelle (2023)
In the "Pre-feasibility study for the implementation of a producing snacks company based on (panela, peanuts and passion fruit) in Paltas Canton and its commercialization in the city of Loja", a mixed methodological approach was used, the type of research was descriptive and the survey technique and direct observation were used; the segment chosen was the economically active population (EAP) and a sample of 383 surveys was calculated. The market study identified an unsatisfied demand of 400,466 pounds of snacks for the first year; the technical study determined the installed capacity to be 438,000 pounds of snacks per year; the company will produce 99,600 pounds per year according to its production capacity. 600 pounds per year according to its used capacity, it will have a market share of 24.87% and will adopt the denomination of limited liability company and its corporate name will be MANIRICH Cía. Ltda.; the investment for the implementation of the project will be $39,694.25, where the selling price to the public will be $1.60 per pound. The results of the financial indicators such as: positive NPV of $45,250.95; IRR of 45.52%, a RBC of $1.18 which means that for every dollar invested 18 cents are earned, the investment is recovered in 2 years, 6 months and 21 days, the sensitivity analysis indicates that the project supports an increase in costs of 5.65% with a sensitivity of 0.99 and can also withstand a decrease in its revenues.